Synthesis and characterization of bifunctional ethenylene bridged mesoporous organoaluminosilicates - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Srilakshmi, Ch.; Singh, A. P. (Nanoscience and Nanotechnology Letters, 2011)
Bifunctional mesoporous organosilicas having -CH=CH- bridges and aluminium in tetrahedral coordination with tailorable pore sizes have been synthesized using a one-step templating method using cationic surfactants of different chain lengths. Unlike the conventional EtOH-HCl template extraction process, EtOH-NH(4)NO(3) was used as the surfactant-extracting medium and chemical analysis results suggest that through this procedure the mesoporous structure can be retained and dealumination can be minimized. The surfactant-extracted mesoporous solids display high surface area, pore volume and the pore size of the material varies in the range 2.6-3.6 nm, with respect to the alkyl chain length of the cationic surfactant. XRD and nitrogen physisorption studies further proved that the organosilicas are hydro thermally stable than the conventional Al-MCM-41 materials and their better stability is attributed to the thick pore walls as well as due to the presence of hydrophobic bridging ethenylene groups in the wall positions. The coupling of Al(4) with -CH=CH- bridges offer new prospects for the application of periodic mesoporous organosilicas in heterogeneous catalysis.
Keywords: Aluminium; Cationic Surfactants; Hydrothermal stability; Organosilicas